Perceptions of residents and hospitality agents towards tourism impacts on sustainability: The Case of UNESCO Literature Creative town of Óbidos - Cláudio, Sílvia de Carvalho (2021)
This master thesis focuses on the perceptions of residents and hospitality agents, of the tourism impacts in the historic walled town of Óbidos, classified as a Portuguese monument and part of UNESCO's Creative Cities network, as Literature Town. In recent years, the historic center of Óbidos has seen an influx of tourists and day visitors, with a consequent overcrowding of the narrow streets, increase of waste, excessive traffic, rise of costs of goods and housing, abandonment of the town center, by the local residents, and fewer local service infrastructures. It is certain that the historic center of Óbidos has seen, over the last decade, an economic boost in the tourism offer, with almost all the businesses and services inside the walls being tourism related. The town hall, the parish church, social security and finance offices are of the few infrastructures used by local residents, who are non-tourism related. The following master thesis examines the positive and negative economic, socio-cultural and environmental perceptions of residents and the hospitality agents, in the historic town. The study was conducted through the use of two different surveys: one administered to local hospitality agents managers and one to the residents, in the historic center. Furthermore, an interview to the town's mayor was also conducted.